Auditoría administrativa y su incidencia en la gestión pública municipal del patronato del Gad de Buena Fe. Año 2013. - Luna Mendoza, Evelin Ramona (2015)
The research was conducted in the canton Buena Fe, Los Rios province, the Municipal Buena Fe is located in the Cooperative October 19, Second Street and Intersection Jimenez 20. The overall objective was to conduct a management audit to Municipal Good Fe and its impact on municipal governance, period 2013. The research methods used were inductive, deductive, scientific, analytic and synthetic; regarding the types of research were the documentary and field; the methodological procedure was stipulated in phases according to the Government Auditing Standard, which is delimited by the creation of the fictional firm, the initial planning which includes a visit to the entity; in phase two, the evaluation of internal control: For phase three the audit process runs with the preparation of working papers, process analysis and description of the findings, and in stage four the report is issued audit by a letter and issue findings with their recommendation. Analyzing the organizational structure and internal policies of the Board in good faith, they are attached and bounded by what is stated in the COOTAD, according to Article 53 jurídica.- Nature The municipal autonomous governments are legal entities of public law, with autonomy political, administrative and financial, so the legislation is respected. It examined the internal control in the Board of Buena Fe showed: deficiencies in its management, so that a confidence level of 72.20% was obtained, and a risk of 27.80% considered Risk Low High; and overall audit risk was 0.31% set as Under. By determining the efficiency and effectiveness of the Public Management Board Buena Fe was determined by management indicators in the training plans, has managed to establish a training in the evaluation period, finding a gap of four it is equal to 20% , meaning a deficiency in the management of municipal public services. The report establishes administrative audit made recommendations for better management of the institution.